Analysis of Daily Test Items In Arabic For Muhammadiyah Elementary School Sidoarum Yogyakarta - Nasikhah, Malikhatun; Wahidah, Zulfa Amalia (Asalibuna, 2020)
To measure the achievement of students' competence in Arabic in accordance with predetermined competency standards, it is necessary to assess the learning outcomes of students. The accuracy of the assessment of learning outcomes has a very significant impact on efforts to improve the quality of education in schools, so the quality of tests as an evaluation tool really needs to be considered. This study aims to determine the quality of the daily test items in Arabic for SD Muhammadiyah Sidoarum Yogyakarta. This research is a quantitative research. Data analysis using the excel application program AnBuSo (Questionnaire Analysis) version 5.0. The results showed that the process of arranging the Arabic questions was not good, because the teacher did not pay attention to the stages used in the preparation of the questions so that the difference between the questions and the difficulty level of the questions was not balanced.